Liquefaction Analysis of Soils according to the New Turkish Building Earthquake Code and Improvement against Liquefaction - Uğur Dağdeviren (Doğal Afetler ve Çevre Dergisi)
One of the damages caused by earthquakes in engineering structures is soil liquefaction-induced damages. Because of the many factors that affect the liquefaction mechanism of soils, the assessment of liquefaction potential is a rather complex problem. In the earthquake, it is the necessary to determine the liquefaction sensitivity of soils and take precautions by estimating possible effects. The stress-based liquefaction analysis, which is the commonly used to determine the liquefaction susceptibility of the soils, has been included in the new Turkish Building Earthquake Code (TBEC). In the usage of this method, the numerous parameters such as the earthquake characteristics, the soil properties, the in-situ and underground water conditions, the properties of equipment used during field studies are needed. Due to the excessive number of parameters and empirical expressions used in the analysis, significant errors can sometimes cause in the soil investigation reports in practice. In this study, in order to make practical use of liquefaction analysis based on standard penetration test defined in TBEC, and to control quickly the performed analyses, the graphics that give the factor of safety against liquefaction of sandy soils were prepared for different depths, groundwater levels, fine contents, and SPT-N values. In addition, cards were developed to determine design parameters such as the stiffness of the columns to be used in the column formation method and the column spacing to be used for the improvement of the liquefiable soils.